EXPERIMENTAL STUDY OF THE SETTLEMENT AND COLLECTION OF PEARL OYSTER SPAT FROM TUTICORIN AREA - Nayar, K Nagappan; Mahadevan, S; Ramadoss, K; Sundaram, N; Rajan, C T (Indian Journal of Fisheries, 2011)
For the first time settlement and growth of pearl oystÂ«rs have be-en observedon granite stones forming the embankments of the New Tuticorin Port. Largenumbers of pearl oyster spat have also been collected by employing diflfeirent typesof spat collectors and the rate of growth of the oysters in the farm has beenstudied